2018
DOI: 10.3389/fped.2018.00290
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Brain Injury of Preterm Infants in the Delivery Room

Abstract: Cerebrovascular injury is one of the major detrimental consequences of preterm birth. Recent studies have focused their attention on factors that contribute to the development of brain lesions immediately after birth. Among those factors, hypothermia and lower cerebral oxygen saturation during delivery room resuscitation and high tidal volumes delivered during respiratory support are associated with increased risk of severe neurologic injury. In preterm infants, knowledge about causes and prevention of brain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Depending on the training courses for healthcare professionals in different countries, and the organization of departments in hospital centers, all or part of these missions can be carried out by other providers, notably respiratory therapists. Previous studies have suggested the importance of the quality of care provided during the stabilization phase, referred to as the "Golden Hour, " for the mortality and morbidity of very preterm infants (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the training courses for healthcare professionals in different countries, and the organization of departments in hospital centers, all or part of these missions can be carried out by other providers, notably respiratory therapists. Previous studies have suggested the importance of the quality of care provided during the stabilization phase, referred to as the "Golden Hour, " for the mortality and morbidity of very preterm infants (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…While there is strong evidence that adults with acute neurological conditions benefit from a specialized neurocritical care, the impact of such care in the neonatal population is less clear [ 8 , 46 ]. However, emerging evidence suggests its potentially positive impact on neurodevelopmental outcome [ 24 , 31 , 46 48 ]. Glass et al demonstrated that the rate of epilepsy after acute symptomatic neonatal seizures was lower in a cohort of newborns managed by a neonatal neurocritical care service [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal diseases, such as preeclampsia, maternal hypotension, severe anemia, asthma, and chronic vascular disease, intrapartum maternal infections, and instrumental delivery can lead to perinatal asphyxia (4). Postnatal asphyxia results from conditions causing neonatal pulmonary failure, including severe hyaline membrane dis-ease, meconium aspiration syndrome, pneumonia, or congenital cardiac disease (5). L-carnitine is a hydrophilic amino acid derivative from lysine.…”
Section: Introductionmentioning
confidence: 99%